The Pageant - Shannon, Charles; White, Gleeson (London : Henry and Co., 1896)
Published by Henry and Co. in London, The Pageant was edited by Charles Shannon and Gleeson White and came out in two annual volumes in 1896 and 1897. (Database of ornament)The Pageant was a London-based literary and art annual of the 1890s. (The online Books page)
Online: https://archive.org/details/Pageant
(Database of ornament) https://beta.1890s.ca/pageantv1_critical_introduction/ (https://ornament.library.ryerson.ca
Engels
Tijdschriften
Keywords: fin de siècle